Molecular characterization and phylogenetics of Fennoscandian cowpox virus isolates based on the p4c and atip genes - Okeke, Malachy Ifeanyi (BioMed Central, 2014)
BACKGROUND: Cowpox virus (CPXV), a rodent-borne Orthopoxvirus (OPV) that is indigenous to Eurasia can infect humans, cattle, felidae and other animals. Molecular characterization of CPXVs isolated from different geographic locations is important for the understanding of their biology, geographic distribution, classification and evolution. Our aim was to characterize CPXVs isolated from Fennoscandia on the basis of A-type inclusion (ATI) phenotype, restriction fragment length polymorphism (RFLP) profiles of atip gene fragment amplicon, and phylogenetic tree topology in conjunction with the patristic and genetic distances based on full length DNA sequence of the atip and p4c genes. METHODS: ATI phenotypes were determined by transmission electron microcopy and RFLP profiles were obtained by restriction enzyme digestion of the atip gene fragment PCR product. A 6.2 kbp region spanning the entire atip and p4c genes of Fennoscandian CPXV isolates was amplified and sequenced. The phylogenetic affinity of Fennoscandian CPXV isolates to OPVs isolated from other geographic regions was determined on the basis of the atip and p4c genes. RESULTS: Fennoscandian CPXV isolates encoded full length atip and p4c genes. They produce wild type V(+) ATI except for CPXV-No-H2. CPXVs were resolved into six and seven species clusters based on the phylogeny of the atip and p4c genes respectively. The CPXVs isolated from Fennoscandia were grouped into three distinct clusters that corresponded to isolates from Norway, Sweden and Finland. CONCLUSION: CPXV is a polyphyletic assemblage of six or seven distinct clusters and the current classification in which CPXVs are united as one single species should be re-considered. Our results are of significance to the classification and evolution of OPVs.